The Use of Easy German Videos to Support the Learning of Writing German Recipes in the German Literature Study Program at Surabaya State University - Parnaningroem, Raden Roro Dyah Woroharsi; Wahyuningsih, Fahmi; Saksono, Lutfi; Pujosusanto, Ari; Ridwan, Agus; Fatina, Amalina Rachmi; Rizman, Rizman (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2025)
This study aims to describe the implementation of Easy German videos as a supporting medium in learning German recipe writing in the German Literature Study Program at Surabaya State University. As a YouTube channel providing authentic German language learning materials, Easy German videos showcase everyday life in Germany through actors using communicative language, gestures, and facial expressions, thereby helping students understand German grammar, vocabulary, and cultural context while practicing listening, speaking, reading, and writing skills. Students’ ability to write German recipes using passive sentences is an interesting topic to discuss, as passive sentences in German have structural differences from Indonesian. This action research, which utilized data from observations, documentation, and interviews, was conducted with 31 students from the German Literature Program in the Writing 4 course during the even semester of the 2024/2025 academic year as respondents. The results of the study indicate that the use of Easy German videos in teaching German recipe writing enhances students’ writing skills, and 87% of respondents stated that the topics presented in the Easy German videos are relevant to supporting German language learning in their classes. Students’ understanding of German culinary traditions is also enriched through exposure to German recipes.